Addison's disease with primary hypothyroidism in a case of visceral leishmaniasis and HIV coinfection. Issue 3 (5th March 2021) - Rani, Monu; Garg, Rakesh; Agraharabachalli Nanjunde, Venkatesh Darshan; Rajput, Rajesh
Abstract : A 41-year-old man presented with vomiting and loose stools. He had a history of long-term intermittent fever, generalised skin hyperpigmentation, dragging sensation in the left hypochondrium and unintentional weight loss. He was receiving combination antiretroviral therapy since 2010 for HIV infection. He also received antitubercular therapy for tuberculous spondylitis. During the hospital stay, he was found to have postural hypotension, hypoglycaemia, hyponatraemia, hyperkalaemia, pancytopenia, hypothyroidism, hyperglobulinaemia and hypoalbuminaemia with reversal of serum albumin/globulin ratio. The morning plasma cortisol was lower than normal and could not be appropriately stimulated after the Synacthen test. The bone marrow histopathology was suggestive of visceral leishmaniasis. He was diagnosed as a case of visceral leishmaniasis and HIV coinfection with primary adrenal insufficiency (Addison's disease) and primary hypothyroidism, as a rare and unusual presentation.